TEACHING RECOUNT TEXTS: USING LEARNING JOURNALS AND STUDENTS' PERCEPTIONS:A Quasi-Experimental Study of Eighth Grade Students at a Junior High School in Bandung - Nova Kusumamandasari, - (2012)
This study investigates the implementation of a learning journal technique in teaching writing of recount texts to improve students' writing ability. Writing is considered as a difficult activity for students because it needs effort and willingness to transform the spoken language into written language without any mistakes of grammatically (Byrne, 1978; Alwasilah & Alwasilah, 2005). Regarding to that reason, writing learning journals which can improve students' ability in writing (Moon, 1999) was implemented in this study. The study employed a quasi experimental design with 44 students of each group as samples at one SMPN in Bandung. The treatments were given in 7 sessions and writing recount text was used as research instrument in the pre-test and post-test. Then, the scores of both groups were calculated using IBM SPSS Statistics 19.0 for Windows. Moreover, the data which obtained through questionnaires were analyzed based on the frequency of students' answers and then calculated and interpreted into percentage. The result of this study shows that after the treatment the experimental group has better writing skill. The statistical computation shows that the learning journal technique is likely to be effective in improving students' writing ability of recount texts (tobt 6.984 > tcrit 2.000 at alpha 0.05). The result of the study is consistent with previous work conducted by Moon (1999), Harmer (2001), and Stewart (1996) that journals can improve students' ability in writing. Moreover, the students' perceptions from the questionnaires also show that the use of learning journal technique is positively responded by the students. Based on these findings, it is recommended that the learning journal technique be applied in teaching writing to improve students' writing ability. The study concludes with some specific recommendation for future research.